2005 POPULAR CHILDREN'S POEM - Sofokleous, Konstantina (My University, 2026)
Animation. Fear and violence in children's stories. An interpretation of a Greek nursery rhyme with old toys and fairytales' heroes used as models for the animation - Cyprus official representation at the 51st Venice Biennial International Art Exhibition, Biennale Arte 2005, La Biennale di Venezia. Curated by Chus Martinez. Organized by Cyprus Ministry of Education and Culture - Greek State Cinema Awards, Nominee